FORMATION OF PRACTICEOLOGICAL COMPETENCE OF MASTERS OF DENTISTRY: MOTIVATIONAL COMPONENT - Iryna Skrypnyk; Yaroslava Kulbashna; Waleria Zacharowa (Borys Grinchenko Kyiv Metropolitan University, 2021)
The article deals with the content of motivational maturity for professional activity of future masters in terms of praxeological competence development. The manuscript also identifies the components and stages of its development. The notion of motivational maturity of future masters in dentistry is defined as a dynamic personal feature, characterized by the development of professionally important qualities, the stability of internal motives for choosing job and the ultimate goals of professional training and external ones like the attractiveness of job in the context of person's life support and professional fulfillment. The motivational and praxeological components of future masters' in dentistry maturity are characterized. Besides, the article presents the results of the survey among the graduates of the dental faculty of Bogomolets National Medical University. It identified a set of motives that contribute to the maturity for performing practical activities. The orientational, synergetic and corrective stages of formation of motivational maturity for future masters in dentistry are revealed. The first one - orientational stage of professional maturity is established as the most important one as it occurs when a student adapts to a new educational environment of a medical university. The next synergetic stage is characterized by accumulation of knowledge and skills necessary for professional competence formation when contingence of training motivation and professional one occurs. The last corrective stage deals with motivation to professional activity based on the integration of motives. It is proved that the presence of stable professional motives in future dentists contributes to their successful mastery of future professional activity and the formation of motivational maturity for it.